GE_GERICHTE P/4803/2010 vom 28. April 2016 - GE Cour de justice (2016)
OBLIGATION DE PRODUIRE DES PIÈCES; SCELLÉS; VOIE DE DROIT; MOYEN DE DROIT; AUTORITÉ DE RECOURS | CPP.248, CPP.264; CPP.265; CPP.393